Wacana Kritis Media Online terhadap Koperasi Merah Putih sebagai Proyek Ekonomi Politik Pembangunan Desa - Farid, Ahmad Salman (JURNAL SYIAR-SYIAR, 2025)
This study analyzes how online media represent and construct meanings around the program using Norman Fairclough’s Critical Discourse Analysis (CDA) approach. Employing a qualitative method, the study applies Fairclough's three-dimensional framework of discourse analysis: textual analysis, discursive practice, and social practice. Ten online news articles from various editorial backgrounds, published between April and May 2025, were analyzed using NVivo software. These articles were sourced from DetikSulsel, TribunKaltim, Tirto, Tempo, Republika, MetroTV News, CNBC Indonesia, RRI Cirebon, ANTARA News, and Kompas.com. The findings reveal that cooperative discourse in the media is predominantly shaped by top-down development narratives with strong symbolic reinforcement from the state. However, ambivalence and media resistance also appear in relation to the potential for policy mismanagement. The choice of diction such as “rural economic legacy,” “distribution monopoly,” and “economic holding” reflects ideological contestation between state interests and civil society concerns. The production of discourse is largely dominated by quotations from state actors, while at the social practice level, the program is closely tied to post-election political agendas and national economic transformation strategies. The discussion shows that media outlets do not merely transmit information but actively shape the structure of meaning and public perception of rural development directions. The prevalence of hegemonic narratives favoring official sources poses a challenge to information democratization, although some media platforms like Tirto and TribunKaltim have voiced critiques and expressed caution regarding potential governance issues within the cooperative system. This study concludes that media representation of the Kopdes Merah Putih program is far from neutral, and instead, it is infused with ideological dynamics and power structures inherent in the discourse of development.